Re-exploring the double-melting behavior of semirigid-chain polymers with an in-situ combination of synchrotron nano-focus X-ray scattering and nanocalorimetry. (August 2016) - Melnikov, A.P.; Rosenthal, M.; Rodygin, A.I.; Doblas, D.; Anokhin, D.V.; Burghammer, M.; Ivanov, D.A.
Graphical abstract: Highlights: A setup for in-situ nano-focus X-ray scattering and nanocalorimetry has been designed. The phenomenon of multiple melting behavior of semirigid-chain polymers was revisited. The melting point depression of polymer crystals can be due to negative pressure. The low-temperature endotherm corresponds to loss of long-range order in lamellar stacks. Abstract: A combination of nano-focus X-ray scattering and nanocalorimetry was used to re-explore the phenomenon of multiple melting behavior of a typical semirigid-chain polymer, poly(trimethylene terephthalate), PTT. The multiple melting of semirigid-chain polymers constitutes one of the long-standing issues in polymer physics. By using very high heating and cooling rates the micro-structure of PTT corresponding to different stages of melting has been arrested by quenching it to room temperature. Although the recrystallization of PTT can be largely precluded under these conditions, the nanocalorimetric curve exhibits two melting events. By employing an in-situ small-angle X-ray scattering, SAXS, it is observed that the low-temperature melting peak corresponds to formation of streaky SAXS patterns. At this stage, the crystalline lamellar stacks lose their long-range order due to melting of the crystals confined in the smallest amorphous gaps, which can be explained by the negative stresses imposed on these crystals. This low-melting crystal fraction can be selectively molten away by performing a fast heating just above the corresponding melting point, and the subsequent heating does not reveal the double-melting behavior anymore. Therefore the phenomenon of the double (or multiple) melting behavior is not necessarily coupled to the melting–recrystallization processes and can be observed even in the absence of any recrystallization.